A cytochrome P450 terpenoid hydroxylase linked to the suppression of insect juvenile hormone synthesis - Sutherland, T. D. (The National Academy of Sciences, 1998)
A cDNA encoding a cytochrome P450 enzyme was isolated from a cDNA library of the corpora allata (CA) from reproductively active Diploptera punctata cockroaches. This P450 from the endocrine glands that produce the insect juvenile hormone (JH) is most closely related to P450 proteins of family 4 and was named CYP4C7. The CYP4C7 gene is expressed selectively in the CA; its message could not be detected in the fat body, corpora cardiaca, or brain, but trace levels of expression were found in the midgut and caeca. The levels of CYP4C7 mRNA in the CA, measured by ribonuclease protection assays, were linked to the activity cycle of the glands. In adult females, CYP4C7 expression increased immediately after the peak of JH synthesis, reaching a maximum on day 7, just before oviposition. mRNA levels then declined after oviposition and during pregnancy. The CYP4C7 protein was produced in Escherichia coli as a C-terminal His-tagged recombinant protein. In a reconstituted system with insect NADPH cytochrome P450 reductase, cytochrome b(5), and NADPH, the purified CYP4C7 metabolized (2E,6E)-farnesol to a more polar product that was identified by GC-MS and by NMR as (10E)-12-hydroxyfarnesol. CYP4C7 converted JH III to 12-trans-hydroxy JH III and metabolized other JH-like sesquiterpenoids as well. This ω-hydroxylation of sesquiterpenoids appears to be a metabolic pathway in the corpora allata that may play a role in the suppression of JH biosynthesis at the end of the gonotrophic cycle.